2009
DOI: 10.1002/asl.207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical mechanisms controlling the vertical redistribution of dust and the thermodynamic structure of the West Saharan atmospheric boundary layer during summer

Abstract: The Saharan atmospheric boundary layer (SABL) plays a significant role in the atmospheric global circulation and directly affects the vertical redistribution of dust originated in the Sahara, the world's largest dust source. Recent measurements have revealed a variety of new dynamical mechanisms that control the structure of the SABL, which are responsible for exchange between the Saharan convective and residual boundary layers. Using new spaceborne laser remote sensing data (CALIPSO) and recently published re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(156 citation statements)
references
References 38 publications
10
144
1
1
Order By: Relevance
“…Above the continent, the mesoscale features associated with the convergence between Harmattan and the West African Monsoon at the ITCZ cause strong updrafts that allow lifting and transport of dust particles throughout the air column (Tulet et al, 2008). The dynamics of the monsoon described by the conceptual scheme of mechanisms controlling the dust vertical redistribution in Cuesta et al (2009) explain the wide occurrence of dust found between 2 and 5 km rather than at the surface. During transport from northern Africa to the Atlantic Ocean, very large amounts of coarse dust (Fig.…”
Section: Continent-ocean Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Above the continent, the mesoscale features associated with the convergence between Harmattan and the West African Monsoon at the ITCZ cause strong updrafts that allow lifting and transport of dust particles throughout the air column (Tulet et al, 2008). The dynamics of the monsoon described by the conceptual scheme of mechanisms controlling the dust vertical redistribution in Cuesta et al (2009) explain the wide occurrence of dust found between 2 and 5 km rather than at the surface. During transport from northern Africa to the Atlantic Ocean, very large amounts of coarse dust (Fig.…”
Section: Continent-ocean Transitionmentioning
confidence: 99%
“…5c, dust is concentrated between the higher layers of the ABL, from 1 to 5-6 km (Gamo, 1996), in response to intense convective mechanisms that are more common in the region at this season (Cuesta et al, 2009). Indeed, the summer solar heating drives the development of the Saharan boundary layer which reaches up to 6 km while the convergence of hot dry air (Harmattan) from the Sahara with fresh moist air (monsoon) from the ocean generates intense convective cells which are responsible for the suspension of large amounts of dust which will be distributed in the ABL.…”
Section: Seasonal Variabilitymentioning
confidence: 99%
“…Such episodes occur frequently over the broader Mediterranean basin , due to its vicinity to the world's major dust sources situated across the northern African (Sahara) and Middle Eastern deserts (Ginoux et al, 2012). Dust particles are mobilized over these areas by strong winds (Schepanski et al, 2009) being uplifted to the free troposphere due to strong convection in the boundary layer (Cuesta et al, 2009) and are transported towards the Mediterranean due to the prevailing synoptic circulation (Gkikas et al, 2015). Under these conditions, dust particles over the Mediterranean are recorded at very high concentrations, as has been confirmed either by satellite (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the inversion of lidar profiles is less accurate for the lower part of these layers due to uncertainties in the lidar ratio for dust and multiple-scattering effects (see e.g. Cuesta et al, 2009Cuesta et al, , 2015. Multiple-scattering effects are neglected in the CALIOP operational products used here.…”
Section: Caliop Dust-layer Heightmentioning
confidence: 99%